2014
DOI: 10.1093/icvts/ivu129
|View full text |Cite
|
Sign up to set email alerts
|

High levels of free haemoglobin in neonates and infants undergoing surgery on cardiopulmonary bypass

Abstract: A high rate of fHb is released during paediatric surgery with CPB in infants. fHb mainly depends on the left atrial venting flow rate and CPB duration. However, such peaks of fHb levels were not associated with renal dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 14 publications
3
18
0
1
Order By: Relevance
“…Consistent with prior studies, ΔPHb was associated with CPB duration [3, 8, 19], likely from the mechanical destruction of red cells. Release of PHb disrupts the biological effects of nitric oxide (NO) and contributes to oxidative injury [12, 2022].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with prior studies, ΔPHb was associated with CPB duration [3, 8, 19], likely from the mechanical destruction of red cells. Release of PHb disrupts the biological effects of nitric oxide (NO) and contributes to oxidative injury [12, 2022].…”
Section: Discussionsupporting
confidence: 89%
“…Possible contributors include hypoperfusion or ischemia-reperfusion induced inflammation. Age, particularly neonates, and CPB duration are associated with increased risk of AKI [3, 8, 9]. Because AKI can occur without measurable hypoperfusion, its association with longer CPB durations suggest that CPB can directly injure the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide scavenging also promotes systemic inflammation and a prothrombotic state . Glomerular Hb filtration may cause renal injury due to both iron‐facilitated generation of reactive oxygen species and tubular obstruction . Cardiac surgical patients in particular suffer haptoglobin depletion, making them particularly sensitive to the deleterious effects of free Hb …”
Section: Discussionmentioning
confidence: 99%
“…The potential mechanisms of haemoglobin‐mediated AKI include intratubular haemoglobin precipitation causing obstruction, iron‐facilitated oxidant damage to tubular epithelial cells and induction of vasoconstriction due to reduced nitric oxide bioavailability . CPB‐related haemolysis is caused by mechanical shear stress within the extracorporeal circuit including roller pumps, turbulent passage through the oxygenator, reservoir, filters, arterial and venous cannulae, cardiotomy suction, the air‐to‐blood interface, cell salvage and transfusion . There is also an increase in RBC fragility and aggregability due to contact with the foreign extracorporeal circuit…”
Section: Risk Factors For Cardiac Surgery‐associated Acute Kidney Injurymentioning
confidence: 99%
“…48 CPB-related haemolysis is caused by mechanical shear stress within the extracorporeal circuit including roller pumps, turbulent passage through the oxygenator, reservoir, filters, arterial and venous cannulae, cardiotomy suction, the air-to-blood interface, cell salvage and transfusion. 49 There is also an increase in RBC fragility and aggregability due to contact with the foreign extracorporeal circuit. 50 Vermuelen Windsant et al found that haemolysis indicated by free haemoglobin plasma levels and nitric oxide consumption significantly increased in cardiac surgery patients undergoing CPB (P < 0.0001).…”
Section: Haemolysis Acute Kidney Injury and Cardiopulmonary Bypassmentioning
confidence: 99%